Proving Peaceful Islam through the Application of Al-'Illat Wa Al-Ma'lûl Approach in Reading Qur’anic Verses of War (Interpretation of Q.2: 190-194 and Q.9: 5-15) - Iftitah Jafar; Mudzhira Nur Amrullah (Universitas Islam Negeri Sunan Kalijaga, 2019)
This paper will prove Islam as a religion of peace by using al-illat wa al-ma'lûl approach in reading Qur’anic verses of war. Qur’anic verses of war have been a crucial problem in interfaith relation. Non-Muslims used such verses as a weapon to label Islam as a violent religion. Moreover, some terrorists justified their violent action with verses of war. However, Muslims insist that such verses basically do not express violence especially if they are properly understood. Radical understanding of Qur’anic texts is partly caused by the approach that exegetes use. Apart from the approach is the use of literal translation and atomistic approach. Atomistic approach suggests the readers to split a verse and treat it separately without relating it to other parts of the verse. Moreover, it does not pay a specific attention to the historical context of the texts (asbȃb al-nuzȗl). In addition, it neglects the correlation of the verses (munᾱsaba). Some approaches have contributed to the problem includes: 1. System approach, 2. Esoteric interpretation approach, and 3. Historic-contextual approach. However, these three approaches did not solve the problem. Therefore, the writer introduces al-illat wa al-ma'lûl approach. The research question is how to prove Islam as a religion of peace by implementing al-‘illat wa al-ma‘lȗl approach in understanding Qur’anic verses of war? Methodologically, this approach was adopted from the concept of cause and effect in various studies, specifically: Physics, History, Philosophy, Communication as well as Islamic studies, especially: Uṣȗl al-Fiqh, Ḥadȋth and Tafsȋr. The approach runs through 4 steps: 1. Literal analysis of key words, especially